Perineural Invasion Is an Independent Pathologic Indicator of Recurrence in Vulvar Squamous Cell Carcinoma. (August 2015) - Holthoff, Emily R.; Jeffus, Susanne K.; Gehlot, Ashita; Stone, Rebecca; Erickson, Stephen W.; Kelly, Thomas; Quick, Charles M.; Post, Steven R.
Abstract : Objectives: Vulvar squamous cell carcinoma (vSCC) is a gynecologic malignancy diagnosed in nearly 4500 women in the United States each year. Current criteria for treatment planning provide inadequate assessment of aggressive vSCC cases, resulting in insufficient use of adjuvant treatments and high rates of vSCC recurrence. Perineural invasion (PNI) is a pathologic feature inconsistently included in the assessment of vSCC, because its relevance to clinical outcomes in these women is not well defined. The purpose of this study was to determine the association between PNI and relevant clinical parameters such as recurrence. Methods: A total of 103 cases of vSCC were evaluated for PNI using pathology report review and immunohistochemistry dual-chromogen staining for S100 and AE1/3. Medical records were reviewed for clinical and follow-up data. Data were analyzed using univariate and multivariate logistic regression statistical methods. Results: Patients with vSCC containing PNI had a greater risk for cancer recurrence than those whose tumors did not contain PNI (odds ratio=2.8, P =0.0290). There was no significant correlation between the presence of PNI and nodal involvement, stage, or lymphovascular invasion. Tumors with PNI had greater depth of invasion (DOI) ( P =0.0047); however, DOI was not associated with recurrence ( P =0.2220). When analyzed using a multivariable logistic regression model, PNI was an independent predictor of recurrence in vSCC (adjusted odds ratio=2.613, P =0.045). Conclusions: PNI is an independent indicator of risk for recurrence in vSCC. The association of PNI with increased risk for recurrence, independent of DOI, nodal involvement, lymphovascular invasion, or stage, should encourage practicing pathologists to thoroughly search for and report the presence of PNI in vSCC.